The Influence of Change-Related Organizational and Job Resources on Employee Change Engagement - Albrecht, Simon L.; Connaughton, Sean; Leiter, Michael P. (Frontiers in Psychology, 2022)
Employee attitudes to change are key predictors of organizational change success. In this paper, change engagement is defined as the extent to which employees are enthusiastic about change, and willing to actively involve themselves in ongoing organizational change. A model is tested showing how change-related organizational resources (e.g., senior leader support for change, organizational change climate) influence change engagement, in part through their influence on change-related job resources. CFA and SEM results yielded good fit to the data in two independent samples: 225 Australian working professionals, and 201 employees from a Prolific sample. As proposed, change-related organizational resources (modelled as a higher order construct) were positively associated with higher order change-related job resources. Change-related job resources were positively associated with change engagement. In contrast to expectations, organizational resources were not directly associated with change engagement. Instead, change-related job resources fully mediated the relationship. Overall, the study provides empirical support for new measures of organizational change resources and employee change engagement. By drawing from well-established models in the change and engagement literatures, the study provides a promising research direction for those interested in further understanding positive employee attitudes to organizational change. Practical implications and future research opportunities are discussed.